Rules and regulations covering the operations of the West African Clearing House - West African Clearing House (Freetown: West African Clearing House)
This publication describes the rules and regulations covering the operations of the West African Clearing House which was set up to to settle payments for goods and services on a multilateral basis on 25 June, 1975. The 12 countries involved in the agreement include Benin, Gambia, Ghana, Ivory Coast, Liberia, Mali, Niger, Nigeria, Sierra Leone, Togo, and Upper Volta (Burkina Faso).
lje 14/3/19
Arch
Keywords: Monetary cooperation; West Africa